EFEKTIFITAS PENGGUNAAN APLIKASI DISCORD DALAM MENINGKATKAN KOMUNIKASI INTERPERSONAL DI KALANGAN PECINTA FILM - Nur Maghfirah Aesthetika; Rizal , Mochamad Syahrul (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
In the development of social media, it is used by the younger generation as a place to interact and create creative digital content. One of them is the younger generation who like the world of cinema, they can interact and exchange opinions between film lovers and get the latest information about films that will be shown. The Discord application is a social media platform, which was previously established as a place for game lovers as a communication tool in the form of voice calls, video calls and written messages. However, the development of Discord Application technology is not only used by game lovers, so the Discord platform has sprung up online communities that use Discord as a forum for film discussion. With the Discord Application, movie lovers can interact with each other. The purpose of this study is to find out how effective interpersonal communication is in discord applications in the film lover community. This study uses a quantitative survey method, in this survey method is used to collect information by observing and examining a subject.